Cultural safety involves new professional roles: a rapid review of interventions in Australia, the United States, Canada and New Zealand. (March 2023) - Tremblay, Marie-Claude; Olivier-D'Avignon, Geneviève; Garceau, Laurence; Échaquan, Sandro; Fletcher, Christopher; Leclerc, Anne-Marie; Poitras, Marie-Eve; Neashish, Eniko; Maillet, Lara; Paquette, Jean-Sébastien
Cultural safety is a decolonizing and transformative approach to health care aimed at achieving health care that recognizes, respects and nurtures the needs, rights and identities of Indigenous peoples. Such a transformation requires new or radically reimagined professional roles. Based on a rapid review design, this synthesis aimed to identify fundamental characteristics of cultural safety interventions that involved the creation or transformation of professional roles. The 23 included studies presented three main categories of professional roles for cultural safety. These roles were focused on (a) supporting health care system navigation, (b) providing a new or improved service offering, and (c) building organizational capacity to provide culturally safe health care. Our results demonstrate that cultural safety can be implemented by key actors playing different roles at different levels of the health care organization. These roles should be viewed as complementary to one another and be defined and implemented in partnership with Indigenous partners.